Please help me find the roots of following polynomial equation:
e^2x-5(e^2x)+6 = 0
Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
is that a typo? I dont think there is a '2' in the middle term..
Its not a typo.Its from our exam paper.
@amistre64...May you please,please,please see my problem? Please??????? :)
Not the answer you are looking for? Search for more explanations.
then combine like terms ..... a = e^2x
-4a+6 = 0
a = 6/4 = 3/2
e^2x = 3/2
2x = ln(3/2)
x = ln(3/2)/2
if i can find it ;)
perhaps it is in my profile...try 2 click once there :)
I am not getting your solution. Can you please explain?
not getting as you dont follow it? or the answer is wrong?
I do not follow it.Its kinda tough.
pleasse come back later to my question, dont quite understand what you mean
e^2x can be substituted for becasue it doesnt change in the problem; its an unknown that we determine; so to clean up the equation, make it = a and use 'a' instead.
a -5a +6 =0
-4a +6 = 0
-4a = -6
a = -6/-4 = 6/4 = 3/2
since e^2x = a ; we told it to ...
e^2x = 3/2
we solve for x by using logarithmic properties..
ln(e^2x) = ln(3/2)
2x = ln(3/2)
x = ln(3/2)
Its involved I guess.I would look into it.Thanks for your help.I appreciate it.
But I really think that this could have been a typo; which would make this part easier:
a = e^x
a^2 -5a +6 = 0
(a-6)(a+1) = 0
a = 6 and a = -1
e^x = a
e^x = 6 ; x = ln(6)
e^x = -1, which is impossible so disregard the -1
x = ln(6)